Adult Learners And E-Learning Readiness: A Case Study. - Asaari, Muhammad Hasmi Abu Hassan; Karia, Noorliza (2005)

(untitled)
Distance education program has been in demand as the working adults can gain tangible and intangible benefits. Thus the challenge for higher learning institution is to provide an elearning environment to these students. Moreover higher learning institutions need to blend the conventional classroom environment with the e-learning method.